RELEVANSI PEMIKIRAN FILSAFAT PENDIDIKAN BAHASA DALAM PERENIALISME DAN ESENSIALISME - Dimas Putra Hidayat; Wulan Mukti Lestari; Shabira nur izzah; Abu Bakar, M. Yunus (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This study comprehensively examines the relevance of language education philosophy in perennialism and essentialism as a strategic response to the challenges of moral degradation and the increasingly complex uncertainty of contemporary knowledge in the era of globalization. The main objective of this study is to systematically analyze the basic concepts, key figures, educational goals, core characteristics, and teaching methods of both schools of educational philosophy in order to develop a synthesis of a holistic approach that is applicable in modern curricula. The main research problem lies in the imbalance between the internalization of universal eternal values and the mastery of practical functional skills in the language learning process in contemporary schools. The method used in this study is a qualitative literature study with a descriptive-analytical, hermeneutic-philosophical, and comparative approach to primary data from indexed scientific journals, authoritative educational philosophy books, and the seminal works of Plato, Aristotle, Thomas Aquinas, Johann Amos Comenius, John Locke, and William T. Harris. The findings of this study show that perennialism emphasizes the Great Books program and Socratic dialectics to shape noble character across generations, while essentialism prioritizes mastery of reading, writing, and arithmetic through direct instruction and systematic drills for optimal social adaptation. The synthesis of the two approaches resulted in a hybrid curriculum of deep literacy and functional competence. In conclusion, the integration of perennialism and essentialism can produce wise, ethical, and adaptive language learners, with recommendations for implementation through comprehensive teacher training programs and empirical testing in Indonesian schools.